Designed Landscapes in the Czech Republic and International Project Pearls of the Landscape - Šimek, Pavel (4D Journal of Landscape Architecture and Garden Art, 2008)
The faculty of Horticulture of Mendel University of Agriculture and Forestry of Brno participates in an international project aiming to establish an international knowledge platform focused on the protection, management, and overall promotion of historic gardens in the Visegrad countries. The project’s main participant and co-ordinator is the Hungárián Corvinus University in Budapest (Associate Prof. László Kollányi). The project issues from the EU Local Agenda Directive that supports the establishing of specialized cultural networks.